Budgetary impact and cost drivers of drugs for rare and ultrarare diseases - Schlander, Michael; Dintsios, Charalabos-Markos; Gandjour, Afschin (Value in health, 2018)
Objectives - To review recent studies reporting health care expenditures (budgetary impact) for orphan medicinal products (OMPs) in Europe and to contribute to our understanding of the cost drivers of nononcological OMPs by means of an empirical analysis in Germany. - Methods - A systematic search for relevant studies on rare diseases was conducted in PubMed and Embase (until December 2016). In addition, annual treatment costs of nononcological OMPs in Germany were analyzed with respect to five explanatory variables: total prevalence of disease, prevalence with added benefit, availability of alternative treatments for the same indication, extent/probability of treatment benefit, and evidence for a treatment effect on mortality. - Results - A total of nine studies with specific estimates of the budget impact of OMPs for a total of 11 countries were identified; one study addressed specifically ultrarare diseases. Annual per-capita spending for OMPs ranges from €1.32 in Latvia to €16 in France. Per-patient annual treatment costs vary between €27,811 and €1,647,627 in Germany. On the basis of the German data set, the regression analysis shows that log prevalence has a significant inverse relationship with log annual treatment cost. In this model, doubling the prevalence leads to a 43% decrease in annual treatment cost. - Conclusions - Despite per-patient annual treatment costs ranging up to several hundreds of thousands of euros for some OMPs, per-capita spending for OMPs is relatively small. In this study an inverse relationship between prevalence and annual treatment costs was found.
Gesehen am 19.03.2020